How Students – Future Teachers Identify themselves… with the Issue of Organic Reaction Mechanisms in the Context of Chemistry Lesson Carried out at Schools - Krzeczkowska, Małgorzata (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
Lesson is the basic unit in the teaching and learning process. Both the teacher and students participate in it, therefore they all should be prepared for the class. The requirement of good substantive preparation for a lesson is not only empowered legally, but it also results from teacher’s own reflection on the improvement of educational process in the context of its effectivity. Recognition of a future teacher in terms of their personal cognitive preferences and professional knowledge is key for the improvement of teaching quality. The main aim of the study was to find out factors that determine the students, decision to conduct lessons on the mechanisms of chemical reactions in organic chemistry at upper secondary school level. For this purpose the results from survey were analysed.